Development Strategy for Marine Scientific Equipment and Technologies - Dong Sheng; Liao Zhenkun; Yu Liwei; Li Huajun (中国工程科学, 2023)
Marine research equipment is critical for the development of marine science. In recent years, China has made breakthroughs regarding the independent research and development of marine research equipment, and some types of the equipment have reached the advanced international level; however, technologies for the equipment still face various challenges. In this paper, the current status of the marine research equipment is reviewed, including research vessels, underwater vehicles, buoys, marine sensors, and marine observation networks. The problems encountered in the technical development of China’s marine research equipment are analyzed from the aspects of key components, technology research and development, data management, basic support, and demand matching. The future development trends are summarized, namely, green, unmanned, intelligent, and collaborative development for deep sea and polar sea research needs. Meanwhile, the key and core technologies for the overall and each category of marine research equipment are analyzed. To provide references for further promoting the rapid development of marine research equipment, the following development suggestions are proposed: sorting out the technical shortcomings, strengthening the coordination of resources to improve supporting capacity, improving the innovation mechanism to promote interdisciplinarity, strengthening the role of the market to promote the industrialization process, and relying on advanced scientific research platforms to expand international cooperation.